Developing an SSI-Based Learning Model of Android Module to Improve Critical Thingking Skills of Students - Masing, Feliksitas Angel; Aminatun, Tien (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2022)
This research aims to know: (1) developing a reasonable biological learning module to improve the critical thingking skills of students, and (2) the effectiveness of biological learning module based on android mobile on students’ critical thinking skills. This research referred to the method developed by Richey and Klein. The population of this research was the students of Giovanni Kupang Senior High School. The data collection used product feasibility assessment sheets and critical thinking skills tests. The results show that: (1) a reasonable biological learning module to improve the critical thingking skills of students is biological learning module based on android through Socio-Scientific Issues-Based Learning on the Subject of Coastal Ecosystems. This module developed according to the stage of DDR by Richey & Klein that includes the model development, model validation (internal and external validation), and model use, and (2) the module based on android mobile through socio-scientific issues based-learning is effective to improve critical thinking skills.